2006
DOI: 10.1121/1.2178700
|View full text |Cite
|
Sign up to set email alerts
|

Auditory temporal resolution in normal-hearing preschool children revealed by word recognition in continuous and interrupted noise

Abstract: The purpose of this study was to examine temporal resolution in normal hearing pre-school children. Word recognition was evaluated in quiet and in spectrally identical continuous and interrupted noise at signal-to-noise ratios (S/Ns) of 10, 0, and -10 dB. Sixteen children four to five years of age and eight adults participated. Performance decreased with decreasing S/N. At poorer S/Ns, participants demonstrated superior performance or a release from masking in the interrupted noise. Adults performed better tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 30 publications
3
34
2
1
Order By: Relevance
“…An important caveat, however, is that the model did not produce higher estimates of criterion SNR at threshold for younger listeners. Previous studies of children have argued that efficiency is poorer in younger listeners in a number of behavioral tasks, including those using psychophysical Grose, 1991a, 1994;Hartley and Moore, 2002;Hill et al, 2004) and speech stimuli (Stuart et al, 2006;Stuart, 2008). A failure to produce higher estimates of criterion for younger children in the present experiment could indicate a poor model fit.…”
Section: A Temporal Resolution As a Function Of Agecontrasting
confidence: 51%
“…An important caveat, however, is that the model did not produce higher estimates of criterion SNR at threshold for younger listeners. Previous studies of children have argued that efficiency is poorer in younger listeners in a number of behavioral tasks, including those using psychophysical Grose, 1991a, 1994;Hartley and Moore, 2002;Hill et al, 2004) and speech stimuli (Stuart et al, 2006;Stuart, 2008). A failure to produce higher estimates of criterion for younger children in the present experiment could indicate a poor model fit.…”
Section: A Temporal Resolution As a Function Of Agecontrasting
confidence: 51%
“…While masker modulation is often associated with improved speech perception in adults, the magnitude of this benefit differs widely across stimuli and conditions (e.g., Buss et al, 2009). Some data indicate a child/adult difference in the ability to benefit from masker modulation (Hall et al, 2012), although this is not always observed (Stuart et al, 2006;Stuart, 2008). It is therefore of interest to evaluate the benefit associated with masker modulation across listener age.…”
Section: Resultsmentioning
confidence: 99%
“…A literatura indica que o reconhecimento de fala das crianças normo-ouvintes é mais afetado por condições adversas como no ruído e/ou em ambiente reverberante quando comparadas aos adultos e esse desempenho pior em crianças para percepção da fala no ruído é esperado até os dez ou doze anos de idade (13)(14)(15)(16)(17)(18)(19)(20)(21). Os estudos supracitados não utilizaram ruído difuso, como as quatro caixas de campo livre adotadas no presente trabalho.…”
Section: Discussionunclassified